Legal Protection Analysis for Investors against Rug Pull Cryptocurrency Fraud in ASIX Token Cases in Indonesia - Tasya Cantik Alya Nabila; Falah Al Ghozali; Wardah Yuspin (Universitas Muhammadiyah Surakarta, 2025)
The development of blockchain and cryptocurrency technology has brought significant transformation to the investment world but has also introduced various legal risks, particularly those related to crypto fraud. This study aims to analyze the legal liability mechanisms for perpetrators and the legal protection for investors in dealing with various types of rug pull schemes in the digital token market, especially in the ASIX token case. The researchers used a normative juridical method, examining the current regulatory framework, identifying legal loopholes, and formulating comprehensive legal accountability for perpetrators and protection for investors. This study adopts a statutory approach to further examine legal protection for investors against cryptocurrency fraud in the ASIX token case. Based on the findings, legal liability for perpetrators of ASIX token fraud refers to several regulations, including the Electronic Information and Transactions Law (ITE Law), the Criminal Code (KUHP), the Consumer Protection Law, and the Anti-Money Laundering Law, with criminal sanctions in the form of imprisonment and fines. Preventive and repressive measures, as well as regulations and supervision by Bappebti, are governed under Bappebti Regulation No. 5 of 2019, Bappebti Regulation No. 7 of 2020, and OJK Regulation No. 37/POJK.04/2018. This protection includes risk assessment, anti-money laundering measures, dispute resolution mechanisms through litigation and non-litigation, and strict oversight of digital asset trading to enhance transparency and security for investors.